Sepsis following cancer surgery: the need for early recognition and standardised clinical care. Issue 4 (2nd April 2016) - Hiong, A.; Thursky, K. A.; Teh, B. W.; Haeusler, G. M.; Slavin, M. A.; Worth, L. J.
ABSTRACT: Despite the implementation of multimodal bundles of care in hospitalised patients, post-operative sepsis in patients with cancer still accounts for a significant burden of illness and substantial healthcare costs. Patients undergoing surgery for cancer are at particular risk of sepsis due to underlying malignancy, being immunocompromised associated with cancer management and the complexity of surgical procedures performed. In this review, we evaluate the burden of illness and risks for sepsis following surgery for cancer. Current evidence supporting standardised strategies for sepsis management (including early recognition and resuscitation) is examined together with challenges in implementing quality improvement programs.